Effect Different Extracts of Tribulus Terrestris on ammonia Volatilization in Loamy Soil - A. Sfook, Asaad; Gha. Neghamish, Razzaq (International Journal of Psychosocial Rehabilitation, 2020)
The study was tested by studying the effect of three different plant extracts on ammonia volatilization and the number of bacteria after adding extracts to soil with urea in Iraqi loamy soil. Three plant extracts (Olea europaea, lepidium aucheri, and Tribulus terrestris) were tested on many isolated bacteria from soils (Bacillus cereus, Bacillus spp, Proteus mirabilis, Proteus vulgaris, Klebsiella pneumoniae, Pseudomonas aeruginosa, E. coli, and Staphylococcus aureus). All bacteria were classified (Schwartz et al., 1965), and a biochemistry test was performed on different bacteria. The results explained that all parts of Tribulus terrestris extracts caused a decreasing number of isolated bacteria from soil after the addition of urea and extracts to loamy soil and were a reduction in ammonia volatilization from soil, but other plant extracts, Olea europaea and Lepidium aucheri, didn’t cause any reduction in the number of isolated bacteria and ammonia volatiles after the addition to soil. So this reason was to exclude these extracts from using to test against ammonia volatilization, but all parts of Tribulus terrestris gave a significantly different activity of reducing ammonia volatile (p < 0.05) from soil compared with control. Seeds with alcoholic extract was the best treatments at reduction number of bacteria and volatile ammonia. Increasing concentration of extracts caused a significant reduction (p < 0.05) with ammonia volatilization and number of bacteria.